Maternal attitudes program in the Pacasmayo prison - Espinoza Yong, Nelson Pacífico (2020)
The present research aimed to improve the Maternal Attitudes of the inmates ofthe Pacasmayo Penitentiary Establishment, by formulating and application of aprogram. The mothers were evaluated using the “Roth”Maternal Attitudes Inventory. The experimental design research consisted of 35 inmates. The results show deficiency in the dimensions of over indulgence and overprotection, after the execution of the program, significant changes were detected in the two factors mentioned, increasing the number of mothers who present positive behaviors, decreasing the mothers who excessively reward their children, said This change will project a better relationship and therefore leads to more potential development despite the mother's deprivation of liberty.